Terahertz Wave Propagation Characteristics on Rough Surfaces Based on Full‐Wave Simulations. Issue 6 (24th June 2022) - Xie, Pengxiang; Guan, Ke; He, Danping; Yi, Haofan; Dou, Jianwu; Zhong, Zhangdui
Abstract: Terahertz (THz) communications are considered as a critical technology for the future wireless communication. The THz band (0.1–10 THz) offers ultra‐wide bandwidths and promises to satisfy the need for ultra‐high‐speed wireless communication. Although propagation characterization is necessary for the THz system design and validation, the response mechanism between the surface roughness and the THz wave is rarely studied. According to the Rayleigh Criterion, most surfaces in a physical environment may be considered to be rough. Scattering on rough surfaces will play a significant role in the THz propagation. Due to the difficulty of practical measurements at the THz band, we use a full‐wave simulation method to study the propagation characteristics of scattering on rough surfaces. First, the Monte Carlo method is used to model rough surfaces with different root‐mean‐squared heights δ and correlation lengths l . Then, with full‐wave simulations, frequency dependency, incident angle dependency, material dependency, and surface size dependency are discussed. By changing the roughness of surfaces, scattering on different rough surfaces at 300 GHz are simulated. Based on a large number of simulation results, we investigate the effect of δ and l on scattering on rough surfaces. Afterward, the cross‐polarization discrimination of each case is analyzed and counted to evaluate the depolarization effect. This study shows that scattering can become a prominent propagation mechanism with the growth of roughness. Besides, the depolarization effect becomes much more severe for a rougher surface. Studying THz propagation characteristics on rough surfaces is critical to accurate THz channel modeling, which further supports the design and deployment of THz communication systems. Key Points: Through full‐wave simulations, propagation characteristics of THz wave on rough surfaces are analyzed in terms of the dependency of frequency, incident angle, material, and surface size The impacts of the root‐mean‐square height and the correlation length on the scattering are discussed Cross‐polarization discrimination of each case in the simulation is calculated and analyzed to evaluate the impact of roughness on the depolarization effect